Islamicate societies a case study of Egypt and Muslim India : modernization, colonial rule, and the aftermath - Kassim, Husain 1939- (Lexington Books, 2012)
"The book can be used as a textbook for the courses in the Islamic Studies at the undergraduate and graduate level. The unique feature of this book, unlike other books on the subject, is that it combines and presents a complete picture of the 'Islamicate' nature of the Egyptian and Muslim Indian societies by demonstrating the changes that took place in various aspects under the impact of the West and colonial rule. The book would potentially find currency in Muslim countries, especially in Egypt and the Indo-Pakistan subcontinent"--Provided by publisher.